Colistin-resistant Escherichia coli mediated by the mcr-1 gene from pigs in northeastern Argentina = Resistencia a colistina mediada por mcr-1 en Escherichia coli aislada de cerdos del nordeste argentino - Pellegrini, Juan Leandro; Gonzalez, Maria De Los Angeles; Lösch, Liliana Silvina; Merino, Luis Antonio; Di Conza, José Alejandro (Elsevier, 2025)
The emergence and spread of multidrug-resistant Escherichia coli carrying mcr-1 is recognized as a threat to public health. The aim of this study was to determine the prevalence of the mcr-1 gene in colistin-resistant E. coli isolates from commercial pig farms in Chaco, Argentina from 2020 to 2021. A total of 140 rectal swab samples were collected from pigs in six different pig production farms. Antimicrobial susceptibility was determined by broth microdilution. mcr-1 to mcr-5 genes were identified by multiplex PCR and clonality was assessed by ERIC and REP-PCR. The prevalence of mcr-1 was 16.4% and mcr-2, mcr-3, mcr-4 and mcr-5 genes were not detected. Colistin MIC values showed a bimodal distribution with a MIC50, MIC90 and a range of 4, 8 and 4–8 μg/ml, respectively. The resistance profile to other antimicrobials was: ampicillin, 87% (20); ampicillin–sulbactam, 47.8% (11); amoxicillin–clavulanic, 13% (3); chloramphenicol, 82.6% (19); ciprofloxacin, 60.9% (14); minocycline, 26.1% (5) and trimethoprim/sulfamethoxazole, 43.5% (10). Eighty-seven percent (87%) of the strains were categorized as MDR and 12 phenotypic resistance patterns with different clonality profiles were observed. A high prevalence of mcr-1 is demonstrated in colistin-free pig farms from Chaco, Argentina. The mcr-1 positive E. coli isolates showed an alarming level of multidrug resistance and high clonal diversity. It is necessary to continuously monitor the presence of the mcr-1 gene not only in pig production, but also in humans and the environment.